PENGEMBANGAN WEB SEKOLAH TERINTEGRASI SISTEM INFORMASI AKADEMIK DI SMAN 10 SINJAI - Nununk Febryanti; Jumadi M Parenreng; Firdaus (Sakura Publisher, 2023)
This study aims to determine the results of the development and test results of an integrated school web academic information system at SMAN 10 Sinjai. This research uses a type of R&D research (research and development) using data collection techniques consisting of observation, interviews, questionnaires, and documentation techniques, and using a prototype development model consisting of stages of gathering needs, building prototypes, evaluating prototypes, coding systems, testing systems, evaluating systems, and using systems. The data analysis used is based on the ISO 25010 feasibility standard which consists of eight aspects. Based on the test results using ISO 25010 quality standards, the integrated school web academic information system at SMAN 10 Sinjai has met the standards where: a) functional suitability with a value of 94% (accepted), b) performance efficiency carried out using the GTMetriks application obtained a load result of 1.1 seconds (meets the standard), c) compatibility is tested on 5 devices obtained a successful value from all devices, d) usability conducted on 35 respondents by asking 30 questions obtained a value of 73% (feasible), e) reliability test success of 100% (meets), f) security at the medium level, g) maintainability is easy to maintain, and h) portability is tested on 6 browsers obtained no errors on the appearance and function of all browsers. The integrated school web academic information system at SMAN 10 Sinjai can be used in managing data related to school activities and school academic activities. Teachers can easily manage students' academic, and students can easily access grades and other academic activities.